(untitled) (Educational Knowledge, 2021)
This work provides a theoretical foundation for promoting holistic well-being from the perspective of Guidance Counseling and other Educational Sciences. It describes its multidimensional nature, different models, and the individual and contextual bases for its development. Well-being is defined as the state resulting from a vital balance between people’s challenges and resources, leading to the use of their own abilities and sensitivity in their interactions with others, across the various dimensions of human wholeness. Similarities and differences between models of well-being are presented in relation to the areas they encompass. Furthermore, the personal and contextual elements that contribute to its development are discussed. Regarding the scope of well-being for all, the importance of a society characterized by equality among diverse and heterogeneous individuals, reciprocity, and the equitable distribution of resources and opportunities is emphasized.